PENGARUH QUALITY OF WORK LIFE DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI UPTD SERTIFIKASI BENIH DINAS KETAHANAN PANGAN, TANAMAN PANGAN DAN HORTIKULTURA PROVINSI SUMATERA UTARA - Lubis, Geana Syah Putri; Syahreza, Dina Sarah (Politeknik Bisnis Indonesia, 2025)
This research seeks to examine the impact of Work Life Quality and Job Discipline on Staff Performance at the UPTD Seed Certification unit under the Food Security, Food Crops, and Horticulture Agency of North Sumatra Province. The investigation was initiated due to underwhelming staff output, insufficient work life standards, and weak discipline levels identified within the organization. Employing a quantitative methodology, the study involved 70 government employees as participants through a total sampling technique. Data were gathered using observation, interviews, structured questionnaires, and literature review, and analyzed through validity and consistency assessments, classical assumption testing, and multiple regression modeling. The results indicated that both Work Life Quality and Workplace Discipline significantly affect staff output, both individually and collectively. It is therefore suggested that initiatives to enhance working conditions and employee compliance be prioritized to boost overall performance within the entity.